Greening Business For Sustainability: The Strategic Role of Green HRM, Innovation and Employee Behavior in Coal Power Plants in Sumatera, Indonesia - Zeqing, Liu; Alfansi, Lizar; Usman, Berto (International Journal of Science, Technology & Management, 2025)
This study examines the influence of Green Human Resource Management (GHRM) on Sustainability Performance (SP) in coal-fired power plants (PLTUs) in Indonesia, with Green Innovation (GI) and Employees’ Green Behavior (EGB) as mediators. Results show that GHRM significantly drives both GI and EGB, and directly improves SP. Indirect effects are even stronger, as GI and EGB enhance sustainability outcomes across environmental, social, and economic dimensions. These findings confirm GHRM as a critical driver of sustainability in energy-intensive industries. Based on the results, this study contributes theoretically by integrating GHRM with the Triple Bottom Line, extending the Resource-Based View and AMO framework, and linking micro-level green behaviors to macro-level sustainability outcomes. It also highlights the contextual relevance of GHRM in high-impact industries and underscores innovation as a strategic HRM outcome. Practically, energy companies should embed sustainability in HR practices, strengthen eco-innovation, and foster green behaviors through incentives and cultural alignment. Policymakers are encouraged to enhance regulatory support, while collaboration across sectors can accelerate the diffusion of sustainable practices. Overall, aligning HRM with green strategies provides both theoretical enrichment and actionable guidance for advancing corporate sustainability.